ANALISIS PERKEMBANGAN KINERJA KEUANGAN PADA PT UNITED TRACTORS TBK - Asmawati, Asmawati (Balance : Jurnal Akuntansi dan Bisnis, 2020)
This research purpose to know the development of financial performance at PT United Tractors Tbk 2015 - 2017. PT United Tractor Tbk research subject. The data used  data sekunder that the financial statements of PT United Tractors Tbk 2015-2017 . The analysis used Current Ratio (CR), Qui k Ratio (QR) , Debt to total asset ratio (DAR), Debt to equity ratio (DER), Net Profit Margin (NPM), Return on Total Assets ratio (ROA) , Return On Equity (ROE) Ratio . The results of the analysis of the development of PT United Tractors Tbk's financial performance from 2015 - 2017 show that liquidity is included in the liquid category. Solvability Analysis is categorized as solvable while for Profitability analysis with very efficient conditions.